Analisis Kinerja Kinerja Keuangan Bank Syariah dan Peran Kebijakan Ekonomi Islam pada Masa Pandemi Covid-19 - Restu Wulan Daru; Muhammad Iqbal Fasa (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2022)
The Covid-19 pandemic is an epidemic of dangerous diseases that have attacked the world, including Indonesia, which can cause death. Because covid-19 has a significant impact on the development of the world economy. This study has the objective of analyzing the financial performance of Islamic banks and the role of Islamic economic policies. This study uses a descriptive qualitative approach with content analysis techniques and library research. The results showed that the bank's financial performance was still in a healthy condition in facing the possibility of risk of loss during the Covid-19 pandemic situation. And the solutions offered include distribution of direct cash assistance from zakat, infak, sedekah, and wakaf, then through superior business capital assistance for the business sector or Micro, Small and Medium Enterprises, as well as through the development of Islamic financial technology.Keywords: Financial Performance, Islamic Banking, Islamic Economic Policy, Covid-19